Documentation of the evidence-diagnosis link predicts nutrition diagnosis resolution in the Academy of Nutrition and Dietetics' diabetes mellitus registry study: A secondary analysis of Nutrition Care Process outcomes - Colin, Casey; Arikawa, Andrea; Lewis, Sherri; Cooper, Melissa; Lamers-Johnson, Erin; Wright, Lauri; Papoutsakis, Constantina (Frontiers in Nutrition, 2023)
Objectives: To describe nutrition care documentation patterns and investigate predictors of nutrition diagnosis resolution. Methods: This is a secondary data analysis of a two-year pragmatic, quasi-experimental study conducted in outpatient clinics where nutrition care was provided to adults with diabetes Type 1 or 2 from May 2017 to June 2019 (n=564 patients). The main outcome measures were frequency of standardized Nutrition Care Process (NCP) terms, NCP links, nutrition diagnosis resolution and predictors of nutrition diagnosis resolution. Predictors of diagnosis resolution were identified using a multivariable logistic regression model. Results: The most prevalent resolved diagnoses were excessive carbohydrate intake (32%), undesirable food choices (21%) and excessive energy intake (13%). The top etiology was food and nutrition related knowledge deficit (57%) and interventions were drawn mainly from the Nutrition Education domain (64%). 146 patient cases (26%) had at least one follow-up visit and 26% of those with a follow-up (n=38) had a resolved diagnosis. The presence of the evidence-diagnosis NCP link in documentation predicted diagnosis resolution (OR= 2.80, 95% CI 1.30-6.02; p=0.008). Conclusion: Most diagnoses were caused by patients’ lack of knowledge and respective interventions focused on nutrition education. Odds of diagnosis resolution improved when the signs and symptoms of the diagnosis were documented during assessment (evidence-diagnosis NCP link). Training dietitians on applying NCP links may be clinically important to resolve nutrition diagnoses. Presented findings are hypothesis generating.